SUKIPT 2016 - USM WINS 4 GOLD, 7 SILVER AND 15 BRONZE MEDALS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, February 2016 – Universiti Sains Malaysia (USM) bagged 4 gold, 7 silver and 15 bronze medals in the Higher Education Institution Sports Championship (SUKIPT) 2016 which was held at Universiti Teknologi Malaysia (UTM) from January 25 to February 5, 2016.